Deficits in the mimicry of facial expressions in Parkinson’s disease - Steven R. Livingstone; Steven R. Livingstone; Steven R. Livingstone; Esztella eVezer; Lucy M. McGarry; Anthony E Lang; Anthony E Lang; Frank A. Russo; Frank A. Russo (Frontiers in Psychology, 2016)
Background: Humans spontaneously mimic the facial expressions of others, facilitating social interaction. This mimicking behaviour may be impaired in individuals with Parkinson’s disease, for whom the loss of facial movements is a clinical feature. Objective: To assess the presence of facial mimicry in patients with Parkinson’s disease.Method: Twenty-seven non-depressed patients with idiopathic Parkinson’s disease and twenty-eight age-matched controls had their facial muscles recorded with electromyography while they observed presentations of calm, happy, sad, angry, and fearful emotions. Results: Patients exhibited reduced amplitude and delayed onset in the zygomaticus major muscle region (smiling response) following happy presentations (p < 0.001, ANOVA, patients M = 0.02, 95% confidence interval [-0.15–0.18], controls M = 0.26, [0.14–0.37]). Although patients exhibited activation of the corrugator supercilii and medial frontalis (frowning) following sad and fearful presentations, the frontalis response to sad presentations was attenuated relative to controls (p = 0.017, ANOVA, patients, M = .05, [-.08–.18], controls M = .21, [.09–.34]). The amplitude of patients’ zygomaticus activity in response to positive emotions was found to be negatively correlated with response times for ratings of emotional identification, suggesting a motor-behavioral link (r = -0.45, p = 0.02, two-tailed). Conclusions: Patients showed decreased mimicry overall, mimicking other peoples’ frowns to some extent, but presenting with profoundly weakened smiles. These findings open a new avenue of inquiry into the masked face syndrome of PD.